THE IMMUNIZING POWER OF NUCLEOHISTON AND OF HISTON - Novy, F. O. (The Rockefeller University Press, 1896)
The results obtained in the preceding experiments may be briefly summarized as follows: 1. Nucleohiston does not protect against a separate and subcutaneous injection of tetanus toxin, diphtheria toxin, hog-cholera bacillus, or anthrax bacillus. 2. Mixtures of nucleohiston and either tetanus toxin or diphtheria toxin lose their specific toxic action—the latter much more rapidly than the former. Animals that recover after inoculation of such mixtures are not rendered immune. 3. In a mixture of nucleohiston and anthrax bacillus the latter is unaffected, even after the lapse of eleven days. 4. The destruction of specific toxins in a solution of nucleohiston, though in part due to sodium carbonate, is probably chiefly due to the nucleohiston. 5. Histon does not protect against a separate and subcutaneous injection of tetanus toxin, diphtheria toxin, hog-cholera bacillus, or anthrax bacillus. 6. In a mixture of histon and diphtheria toxin the latter is destroyed in a few minutes. This action is in part, if not wholly, due to the acidity of the histon solution. Similar mixtures of closely related bodies, serum globulin or albumoses, in Witte's pepton, give analogous results. The animals that recover from such inoculations are not rendered immune. Histon does not destroy the tetanus toxin as readily as the diphtheria toxin. 7. Histon possesses decided and marked toxic properties which are not due to the hydrochloric acid present.